THE CREDIT INFLUENCE ON THE ECONOMIC GROWTH IN ROMANIA - Gheorghe MOROŞAN; Iulian CONDRATOV; Aurica Trandafira SOFIAN (USV Annals of Economics and Public Administration, 2017)
The purpose of this paper is to highlight the correlations existing between credit and GDP; it will be shown, as well, which is the credit influence on the economic growth. The motivation for this work derives from the fact that, at the national level, has been discussed countless ways for ensuring economic growth. The objectives followed within the present paper takes into account, mainly, to: introduce the main theoretical aspects related to credit; present the main theories of economic growth; analyze and interpret the macroeconomic indicators, relevant for economic growth at the macro level; analyze the existing relations between credit and economic growth as well as the credit influence on GDP. The paper focuses on the existing correlations between credit and economic growth, determined using the SPSS program.